Effect Of Chlorothalonil On Some Cytogenetic Parameters Of Human Peripheral Blood Lymphocytes - Baghdad Science Journal (مجلة بغداد للعلوم)
The study aimed to investigate the effect of fungicides chlorothalonil at different concentrations ( 0.1 , 0.5 , 5 , 25 , 50 ) × 10 - 5 M on some cytogenetic parameters of human peripheral blood lymphocytes . The genotoxicity parameters were estimated by the number of chromosomal aberrations (CAs) and their types and by estimating the induced micronuclei (Mn) . Cytotoxic effect recorded by estimating the mitotic index (MI) . Results revealed that the fungicide increased the CAs in dose – response pattern with positive correlation coefficient ( r = + 0.964) , there was a significant differences among the concentrations (P